Edukasi Literasi Keuangan pada Rumah Ibadah (Masjid) di Parit Baru, Salatiga, Sambas, Kalbar - Sentiya, Novi; Roshani; Munandar (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
Parit Baru Village, Salatiga District, Sambas Regency, has 7 mosques, 3 prayer rooms, and 5 Buddhist temples. Some houses of worship have recorded their financial statements, but they are not yet in accordance with the Accounting Standards for Entities Without Public Accountability (SAK-ETAP). SAKETAP is stipulated by the Indonesian Institute of Accountants (IAI) in ISAK-35 (Interpretation of Financial Accounting Standards) concerning the Presentation of Financial Statements for Non-Profit Entities. Therefore, houses of worship require education and training in mosque financial literacy so they understand and are able to present accountable financial statements. Education and training are carried out through Community Service (PKM) activities in the Public Sector Accounting Study Program. The purpose of the PKM activity is to improve understanding and ability in preparing mosque financial statements. The results of the PKM activity show that there is an increase in knowledge and ability in preparing financial statements according to applicable standards. Before the PKM activity, participants did not fully understand house of worship accounting, because financial recording has only been done in a simple manner. However, after participating in PKM activities, house of worship administrators came to understand the importance of good accounting as a form of accountability to the public. This can be seen from the enthusiasm of the participants who want to learn about the application for compiling financial reports for places of worship that we have provided.